Pengaruh Metode Pelatihan Berbasis Kompetensi dan Gaya Kognitif Terhadap Keterampilan Kesehatan dan Keselamatan Kerja Siswa - Yeti Yuni Perohmatin; Rufi'i Rufi'i; Hartono Hartono (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
This study aims to determine: The influence of the acquisition of K3 skills of students using conventional methods and competency-based training methods, The effect of K3 skills of students with field dependent cognitive styles and independent field cognitive styles, the relationship between methods and styles cognitive ability of students' K3 skills. The procedure used by researchers is a quasi experiment and using a non-equivalent control group design by applying a 2x2 faktorial design in the experimental design. The technique was taken by random class sampling. This thesis analysis was tested with a statistical analysis of Analysis of variance (ANOVA). The results showed (1) there was an influence on the acquisition of K3 skills of students who learner using conventional methods and competency-based training methods (F = 104,942; p = 0,000), (2) there were the influence of K3 Skills of students learning with field dependent cognitive style and independent field cognitive style (F = 75.865; p = 0.000) and there is no correlation between methods and cognitive style on students' K3 skills (F = 3.283; p = 0.073)